The Potential of a Win-Win Solution as a Means of Resolving Political and Legal Conflicts in the 2024 Regional Head Election in South Sumatra: A Strategic Analysis - Imelda*, Chitra; Aritama, Randi; Hasanuddin, Hasanuddin; Waliadin, Waliadin (Universitas Syiah Kuala, 2024)
This research analyzes the win-win solution strategy as a means to address legal political conflicts in the regional head elections in South Sumatra in 2024. With a focus on seeking solutions that benefit all parties involved, the win-win solution approach is identified as an effective method to reduce tension, create conducive conditions for development, and build trust and cooperation among conflicting parties. Through rule adjustments, strengthening legal frameworks, training, and the implementation of information technology, this approach is expected to make a significant contribution to resolving legal political conflicts in an effective, fair, and democratic manner.